Sensory subtypes in children with autism spectrum disorder: latent profile transition analysis using a national survey of sensory features. (27th March 2014) - Ausderau, Karla K.; Furlong, Melissa; Sideris, John; Bulluck, John; Little, Lauren M.; Watson, Linda R.; Boyd, Brian A.; Belger, Aysenil; Dickie, Virginia A.; Baranek, Grace T.
<x xml:space="preserve">Abstract</x> Background Sensory features are highly prevalent and heterogeneous among children with ASD. There is a need to identify homogenous groups of children with ASD based on sensory features (i.e. sensory subtypes) to inform research and treatment. Methods Sensory subtypes and their stability over 1 year were identified through latent profile transition analysis (LPTA) among a national sample of children with ASD. Data were collected from caregivers of children with ASD ages 2–12 years at two time points (Time 1 N = 1294; Time 2 N = 884). Results Four sensory subtypes (Mild; Sensitive‐Distressed; Attenuated‐Preoccupied; Extreme‐Mixed) were identified, which were supported by fit indices from the LPTA as well as current theoretical models that inform clinical practice. The Mild and Extreme‐Mixed subtypes reflected quantitatively different sensory profiles, while the Sensitive‐Distressed and Attenuated‐Preoccupied subtypes reflected qualitatively different profiles. Further, subtypes reflected differential child (i.e. gender, developmental age, chronological age, autism severity) and family (i.e. income, mother's education) characteristics. Ninety‐one percent of participants remained stable in their subtypes over 1 year. Conclusions Characterizing the nature of homogenous sensory subtypes may facilitate assessment and intervention, as well as potentially inform biological mechanisms.